Audit Audit Operasional Terkait Efektivitas, Efisiensi Dan Ekonomisasi Pada Fungsi Penjualan Dan Pelayanan Konsumen: Studi Kasus di Toko Istana Bayi Jl. Arifin Achmad Pekanbaru, Riau - Audina, Bening; Nur Fitriana (Politeknik Raflesia Press, 2025)
This study aims to determine the company’s operational system as well as the level of effectiveness, efficiency and economy of the sales function and customer service at the Istana Bayi store Jl. Arifin Ahcmad Pekanbaru. This research is a qualitative research with descriptive design. The data collection methods used are observation, interviews, questionnaire/checklist by giving a set of statements then filled in and crossed out on the statements in accordance with the conditions applied in the company. The results showed that the operational audit in the company was still not optimal because if examined from the results of observations and interviews that have been conducted that the lack of careful planning, human resource management owned by the company is less than optimal and relatively limited. While the level of operational audit related to effectiveness in the sales function owned by the company during the researh period was classified as less effective, but the level of efficiency during the research periode was classified as efficient and very efficient. While the operational audit releted to economization in the sales funcition during the research period was classified as uneconomical. There are no significant changes regarding the level of effectiviness, efficiency and economization that the company has during the research period 2021-2024.